Hydrogen Sulfide Upregulates Acid-sensing Ion Channels via the MAPK-Erk1/2 Signaling Pathway. Issue 2 (19th February 2021) - Peng, Zhong; Kellenberger, Stephan
Abstract: Hydrogen sulfide (H2 S) emerged recently as a new gasotransmitter and was shown to exert cellular effects by interacting with proteins, among them many ion channels. Acid-sensing ion channels (ASICs) are neuronal voltage-insensitive Na + channels activated by extracellular protons. ASICs are involved in many physiological and pathological processes, such as fear conditioning, pain sensation, and seizures. We characterize here the regulation of ASICs by H2 S. In transfected mammalian cells, the H2 S donor NaHS increased the acid-induced ASIC1a peak currents in a time- and concentration-dependent manner. Similarly, NaHS potentiated also the acid-induced currents of ASIC1b, ASIC2a, and ASIC3. An upregulation induced by the H2 S donors NaHS and GYY4137 was also observed with the endogenous ASIC currents of cultured hypothalamus neurons. In parallel with the effect on function, the total and plasma membrane expression of ASIC1a was increased by GYY4137, as determined in cultured cortical neurons. H2 S also enhanced the phosphorylation of the extracellular signal‐regulated kinase (pErk1/2), which belongs to the family of mitogen-activated protein kinases (MAPKs). Pharmacological blockade of the MAPK signaling pathway prevented the GYY4137-induced increase of ASIC function and expression, indicating that this pathway is required for ASIC regulation by H2 S. Our study demonstrates that H2 S regulates ASIC expression and function, and identifies the involved signaling mechanism. Since H2 S shares several roles with ASICs, as for example facilitation of learning and memory, protection during seizure activity, and modulation of nociception, it may be possible that H2 S exerts some of these effects via a regulation of ASIC function. :